Menelisik Pariwara Rinso Warna Versi Badut dalam Logika Semiologi Barthes - Sampurna, Angelia; Agustina, Merry; Marta, Rustono Farady (Jurnal Komunikasi Profesional, 2020)
In the era of intense competition in the marketing world, companies are driven to create creative advertising effectively. The right advertising will have a long-term marketing impact, and easily influence and take market position. The problem discussed in this study is how Rinso try to influence consumer purchasing decisions by taking advantage through meaning of denotation, connotation, and myth in taking the position of detergents that can maintain color quality through Rinso Color. This study uses Barthes Semiology theory, with descriptive qualitative research methods. The object of research is color, which can be concluded from this analysis, if color is a form to showed how is the character of a personality. Personality that wants to be formed through color, is another effort that needs to be done through Rinso Color. It can be seen that the preparation of aspects of advertising represents all aspects of both character, tagline, diction, to the target market of Rinso which is part of the total branding terminology in integrated marketing communication. Keywords: Barthes Semiology; Integrated Marketing Communication; Rinso Ad.